Educational Solutions for Human Development - Inês Kisil Miskalo (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
The biggest challenge for education in Brazil is not only to popularize school access, but also to provide conditions for students to remain at school successfully. Therefore, it is necessary to invest in teachers qualification and in the adoption of efficient and effective public policies based on managerial patterns designed to cater to human resources articulations, equipment, finance and, mainly, to methodologies focused on results. Quality reorganization of public policy will only be possible through a triplet effort involving political will from public government, cooperation from the private sector and contribution from civil society. These partnerships assure public sphere the development of essential projects to enable the country to grow. They also allow Education to occupy the important place it deserves in the national agenda as a tool to foster human development. It is essential to guarantee to people knowledge and abilities that enable them to make sensible choices, have their health improved and thus, take part in the society actively. This essay intends to provide information on Instituto Ayrton Senna´s mission to boost quality education for new Brazilian generations as a precondition for human development. Its education programs supply managerial praxes to state and municipal public school systems that warrant conceptual changes and alter the school failure vicious cycle.